Pachyonychia congenita with an unusual intraoral manifestation: case report - Santos-Leite, Éder Gerardo; Ramírez Sánchez, Adrian Eduardo; Buentello de la Cruz, José Luis; Farias Bezerra , Hélen Kaline; Martínez Pedraza, Ricardo; Martelli-Júnior, Hercílio (Journal of Oral Diagnosis, 2024)
Pachyonychia congenita (PC) is a rare dermatosis impacting skin structures, appendages, and mucous membranes, primarily characterized by nail dystrophy, palmoplantar keratoderma, and plantar pain. Oral manifestation are particularly natal teeth and oral leukokeratosis and may be the earliest clinical signs. There is no specific treatment, the protocols are individualized and aim to alleviate symptoms. A 5-year-old boy came to the dentist’s office complaining of a toothache. Intraoral examination revealed diffuse lesions scattered in the hard palate, marginal gingiva, alveolar mucosa, and tongue. Additionally, white plaques were observed on the lips at the boundary between the perilabial skin and the vermilion of the lip. Extraoral examination identified palmar lesions, skin lesions on the elbows and knees, as well as nail thickening and absence on the fingers and toes. Incisional biopsies of the lesion on the palate and on the belly of the tongue were performed and histopathological examination showed subepithelial clefts, dyskeratotic areas, hyperkeratosis, and acanthosis. Based on clinical and microscopic features, the diagnosis of PC (OMIM #167200) was established. Despite the typical skin alterations, the intraoral lesions shown in this case are atypical and uncommon. This case describes a young patient with typical skin and nail alterations and atypical and uncommon intraoral lesions related to PC and emphasizes the significant role of dentists in diagnosing syndromic conditions affecting the mouth.